(3TQM GdJfXje GdbGfhfj ddefGbUGJ hGdeRGjOGJ hdGFMJg GdJfajPjIs - (3CMeO YHO GddWja(B, (3GHQGgjes ((3GdbGgQI(B;(3GdLjRI(B:s (3GdecJH GdKbGaj(B;(3OGQ GdCSeGM(B,s, 2004)
(3GdJfXje GdbGfhfj ddefGbUGJ hGdeRjOGJ, JfXje CMcGe YedjGJ GdefbhdGJ (B((3heG McegG(B)(3, JMOjO eGgjI WQb GdJYGbO, JfXje CMcGe YedjGJ TQGA hGSJFLGQ GdYbGQGJ, JfXje CMcGe YedjGJ HjY hJCLjQ GdYbGQGJ hGdeTQhYGJ ZjQ PGJ GdTNUjI GdGYJHGQjI, hGdJQNjU HGdGfJaGY Ch HGSJZdGd GdYbGQGJ, HeG aj Pdc GdefTBJ GdSjGMjI hGdebGUa, CMcGe YGeI ddJYGbO Yf YedjGJ TQGA Ch jY Ch JCLjQ Ch GdGfJaGY Ch GSJZdGd GdCTjGA GdNGVYI dCMcGe GdbGfhf(B.s
(3GdedGMb U(B.201s
Keywords: (3GdbGfhf GdJLGQjs; (3GdeRGjOGJs; (3GdefGbUGJs